Life-Destroying Diagrams - Brinkema, Eugenie, 1980- (Book collections on Project MUSE., 2021)
"In Life-Destroying Diagrams, Eugenie Brinkema brings the insights of her radical formalism to bear on supremely risky terrain: the ethical extremes of horror and love. Through close readings of works of film, literature, and philosophy, she explores how diagrams, grids, charts, lists, abecedaria, toroids, tempos, patterns, colors, negative space, lengths, increments, and thresholds attest to formal logics of torture and cruelty, violence and finitude, friendship and eros, debt and care. Beginning with a wholesale rethinking of the affect of horror, orienting it away from entrenched models of feeling toward impersonal schemes and structures, Brinkema moves outward to consider the relation between objects and affects, humiliation and metaphysics, genre and the general, bodily destruction and aesthetic generation, geometry and scenography, hatred and value, love and measurement, and, ultimately, the tensions, hazards, and speculative promise of formalism itself. Replete with etymological meditations, performative typography, and lyrical digressions, Life-Destroying Diagrams is at once a model of reading without guarantee and a series of generative experiments in the writing of aesthetic theory"--